2021
DOI: 10.34172/ijhpm.2021.114
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Home Screening for Promoting Awareness of Impaired Glycemic Status and Utilization of Primary Care in a Low Socio-Economic Setting: A Follow-Up Study in Reunion Island

Abstract: Background: Low socio-economic settings are characterized by high prevalence of diabetes and difficulty in accessing healthcare. In these contexts, proximity health services could improve healthcare access for diabetes prevention. Our primary objective was to evaluate the usefulness of home screening for promoting awareness of impaired glycemic status and utilization of primary care among adults aged 18-79 in a low socio-economic setting. Methods: This follow-up study was conducted in 2015-2016 in Reunion Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For instance, Cristel et al observed a reduced likelihood of compliance with specialist care referrals among www.nature.com/scientificreports/ patients residing in socioeconomically disadvantaged urban areas and those aged between 18 and 44 years 26 . In a separate study, Adrian et al noted a tendency among patients aged 18 to 39 years to forgo general practitioner consultations for confirming screening results 48 . Our finding also revealed an intriguing observation that non-Chinese individuals (i.e., Malays and Indians) exhibited a greater tendency toward compliance in comparison to the Chinese population.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Cristel et al observed a reduced likelihood of compliance with specialist care referrals among www.nature.com/scientificreports/ patients residing in socioeconomically disadvantaged urban areas and those aged between 18 and 44 years 26 . In a separate study, Adrian et al noted a tendency among patients aged 18 to 39 years to forgo general practitioner consultations for confirming screening results 48 . Our finding also revealed an intriguing observation that non-Chinese individuals (i.e., Malays and Indians) exhibited a greater tendency toward compliance in comparison to the Chinese population.…”
Section: Discussionmentioning
confidence: 97%